2016
DOI: 10.1017/jog.2016.127
|View full text |Cite
|
Sign up to set email alerts
|

Area and mass changes of Siachen Glacier (East Karakoram)

Abstract: ABSTRACT. Here, we present a comprehensive assessment of Siachen Glacier (East Karakoram), in terms of its area and elevation change, velocity variations and mass budget, utilizing different satellite datasets including Landsat, Hexagon, Cartosat-I, Shuttle Radar Topography Mission, Envisat Advanced Synthetic Aperture Radar and Japanese Advanced Land Observing Satellite Phased Array-type L-band SAR. The total areal extent of Siachen Glacier did not change significantly between 1980 and 2014; however the expose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(32 citation statements)
references
References 66 publications
0
32
0
Order By: Relevance
“…Pieczonka et al, 2013). The ICIMOD glacier inventory (Bajracharya and Shrestha, 2011), also available through the GLIMS database (www. glims.org), was used as a baseline data set and was manually adjusted based on the utilized optical imageries for DTM generation and Landsat ETM+ scenes of the years 2000 and 2001.…”
Section: Datamentioning
confidence: 99%
See 1 more Smart Citation
“…Pieczonka et al, 2013). The ICIMOD glacier inventory (Bajracharya and Shrestha, 2011), also available through the GLIMS database (www. glims.org), was used as a baseline data set and was manually adjusted based on the utilized optical imageries for DTM generation and Landsat ETM+ scenes of the years 2000 and 2001.…”
Section: Datamentioning
confidence: 99%
“…a −1 . Agarwal et al (2016) reported a mass budget of −0.03 ± 0.21 m w.e. a −1 of Siachen Glacier for the period 1999-2007.…”
Section: Introductionmentioning
confidence: 99%
“…4) with an area of 1107 km 2 . In addition, Agarwal and others (2016) showed a mass balance of −0.03 ± 0.21 m w.e. a −1 during 1999-2007 for the Siachen glacier (937 km 2 ).…”
Section: The Long-term Glacier Change Anomaly In the Karakorammentioning
confidence: 99%
“…However, several studies based on ICESat/GLAS trends have reported a slightly negative or nearly stable glacier mass balance in the entire Karakoram for 2003-09 ( others, 2012, 2015; Gardner and others, 2013). More recently, by subtracting SRTM DEM from TanDEM-X DEM and Cartosat-1 DEM, respectively, Rankl and Braun (2016) and Agarwal and others (2016) obtained similar results in the Shaksgam valley (central Karakoram, for 2000-12) and the Siachen glacier (eastern Karakoram, for 2000-07). At present, the mass-balance records of the Karakoram glaciers are mainly concentrated in the early 21st century, and the observation times cover ∼10 years, which leaves scope for extending the timescale of the mass-balance monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…ice at similar elevations across HMA (Gardelle et al, 2013;Kääb et al, 2012), in the Khumbu region (Nuimura et al, 2012), the Langtang catchment , the Kangri Karpo Mountains (Wu et al, 2018), for the Kanchenjunga Glacier (Lamsal et al, 2017) and the Siachen Glacier (Agarwal et al, 2017). This has been referred to as the "debris-cover anomaly" .…”
mentioning
confidence: 99%